Penggunaan Kata dan Istilah Bahasa Inggris pada Promosi Penjualan Online di Instagram - Husna, Nurul Fadzilatul; Azizah, Siva Nur; Yahya, Mokh (Yayasan Sukma Bangsa, 2019)
This study aims to find out diction errors in online sales promotions on Instagram. Twenty sentences have been taken from six accounts established in Solo, Central Java, as the samples. Analysis is focused on the inappropriate use of English words and terms. The results of this study are as follows. First, some forms of language errors found in Instagram accounts includes diction and terms errors. Second, the factors of language errors in sales promotions are (1) English is more popular, (2) English is more concise, (3) English looks more prestigious, and (4) English seems more persuasive.